Multidimensional indices in the assessment of chronic obstructive pulmonary disease. (August 2021) - Corlateanu, Alexandru; Plahotniuc, Alexandra; Corlateanu, Olga; Botnaru, Victor; Bikov, Andras; Mathioudakis, Alexander G.; Covantev, Serghei; Siafakas, Nikolaos
Abstract: Chronic obstructive pulmonary disease (COPD), a very common disease, is the third leading cause of death worldwide. Due to the significant heterogeneity of clinical phenotypes of COPD there is no single method suitable for predicting patients' health status and outcomes, and therefore multidimensional indices, assessing different components of the disease, were developed and are recommended for clinical practice by international guidelines. Several indices have been widely accepted: BODE and its modifications, ADO, DOSE, CODEX, COTE. They differ in their composition and aim, while they are more accurate and better validated in specific settings and populations. We review the characteristics, strengths and limitations of these indices, and we discuss their role in routine management of patients with COPD, as well as in specific clinical scenarios, such as resuscitation and ceiling of care, or decisions to offer more invasive treatments. This analysis may help clinicians to use those indexes in a more practical and appropriate way. Graphical abstract: Image 1 Highlights: COPD is characterized by significant complexity and heterogeneity. Clinicians need a personalized approach to COPD to be able to evaluate treatment effectiveness and to predict outcomes. Combinations of several variables have better prognostic capacity than each of them alone. Multidimensional indices are simple to administer and fairly accurate tools for COPD management. Each index has strengths and limitations and the optimal index may differ according to the clinical scenario.